أثر أستخدام اسلوبين من طريقة النمذجة على مستوى الرسم بالالوان المائية لدى طلبة كلية الفنون بجامعة السليمانية - حسين, جواد نعمت (Sulaimani Journal for Humanities, 2003)
The research aimed at a comparison between the effect of using two styles of live model and instructional animated film on the level of landscape painting with water colour within Fine Arts students in the University of Sulaimani. The experimental design with the two equivalent groups of pre and post test was used as an approach to the research. The samples consisted of 20 students (16 male and 4 female) choose intentionally, from the research community with the rate of (66.6%) and divided randomly to two equal groups. The first group represented the first experimental group who studied through the alive model. The other group represented the second experimental group who studied the same subject using the instructional animated film. Variations among both group, such as sex, background, period of experiment, and teachers were controlled. To assess the research sample products within both pre and post test, the researcher prepared a special checklist and its validity was approved externally. The experiment was applied upon both groups at the same time within period °f four classes - four hours ,per class, then both groups were assessed by the post-test and the products were assessed by a professional committee, then the data was statistically terminated by using the (t-test). The research concluded that both groups gained a success after the experiment with a different level of (0,001). The research also concluded the success of the second experiment group over the first one with the level of (0,05).